DEVELOPING ALYA’S INSTAGRAM REELS IN DISTINGUISHING PROGRESSIVE TENSE TO IMPROVE STUDENTS’ ABILITY IN GRAMMAR: Abstract, Abstrak, Introduction, Methodology, Findings and discussion, Conclusion, References - Putri, Alya (JELLE, 2024)
English learning media at this time is very diverse and develops following the development of technology. Moreover, the use of Instagram media as a medium for learning grammar. This research aimed to explain the diffuclties of students in using progressive tense and the development of Alya's reels instagram as a media in teaching in distinguishing progressive tense to improve students' ability in grammar. The research that was carried out by the researcher is a type of research and development (R&D). The subject of this research were the eleventh grade students that consist of 90 students. The instruments used in this research were questionaries, test, and interviews. The data gathered were analyzed qualitatively and quantitatively. This study was research and development used the Borg and Gall development model which has been adapted to field conditions. The stages used include (a) need analysis, (b) development prelieminary form a product, (c) prelieminary field testing, (d) main revision, (e) main field testing. Validation of instagram reel media was carried out by two subjects, namely material experts and media expert. This research concludes that Alyas’ instagram reel is a valid and affective medium to enhance students’ achievement in grammar learning.